THE ALKALI TREATMENT PARAMETERS USING TAGUCHI MODEL IN ORDER TO OBTAIN THE OPTIMUM TENSILE STRENGTH OF SINGLE KENAF FIBER - Pratiwi, Henny (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2015)
The development of high-performance engineering products made from natural resources is increasing worldwide. Kenaf plants have been extensively exploited over the past few years. Chemical treatment is considered to modify the fiber surface properties. In this study, kenaf bast fibers were treated with various concentrations of NaOH with different immersed time, immersed temperature, and dried temperature. Fiber bundle tensile were performed to evaluate the effect of treatments on the fiber tensile strength. Taguchi Methods are used in order to obtain the optimal parameter which could affect the tensile strength of kenaf fibers. Three-Level Orthogonal array is used to design the experiment. Finally, the experimental results will be evaluated using analysis of variance (ANOVA). The analysis of variance (ANOVA) shows that the most significant alkali parameter is NaOH concentration, which accounts for 40.19 percent of the total. It is also found that the optimum treatment is kenaf immersed in 3 wt. percent NaOH solution for 1 hour at 33 degrees celcius and dried at 60 degrees celcius which is supported by the Fourier Transform Infrared Spectroscopy.